1999
DOI: 10.1097/00008483-199911000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Multi-State Outcomes Program for Cardiopulmonary Rehabilitation

Abstract: Although this study does not document the effectiveness of rehabilitation for patients, it does demonstrate that the collection and analysis of standardized outcomes among many cardiac and pulmonary rehabilitation sites is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Although the mental health differences between groups were not statistically significant, participants reported higher mental health scores. The SF‐36 subscale scores for the participants were similar to the mean scores obtained by Jungbauer and Fuller (1999) in their sample of 928 cardiac patients who participated in CR. Thus, these findings document the effectiveness of CR and suggest that CR participants do enjoy higher health‐related function and quality of life after their cardiac event than do nonparticipants.…”
Section: Discussionsupporting
confidence: 64%
“…Although the mental health differences between groups were not statistically significant, participants reported higher mental health scores. The SF‐36 subscale scores for the participants were similar to the mean scores obtained by Jungbauer and Fuller (1999) in their sample of 928 cardiac patients who participated in CR. Thus, these findings document the effectiveness of CR and suggest that CR participants do enjoy higher health‐related function and quality of life after their cardiac event than do nonparticipants.…”
Section: Discussionsupporting
confidence: 64%
“…This assessment tool consisted of a 10‐item checklist of cardiac risk factors derived from the Indiana Cardiac Rehabilitation Knowledge Questionnaire 49 . The reliability and validity of the questionnaire has not been reported, yet the questionnaire has been used previously in studies that have been subjected to peer review 50 . Participants were asked to indicate the cardiac risk factors which they considered could be changed.…”
Section: The Studymentioning
confidence: 99%
“…Aude et al [25] revealed that CR helped participants feel better and they perceived their health improvement; however, the duration of hospital-based CR for patients with AMI varied, and was had a relatively short-term follow-up [26][27][28]. Therefore, we are unable to pool the data to quantify the effect.…”
Section: Discussionmentioning
confidence: 98%